Laparoscopic Bilateral Retroperitoneal Lymph Node Dissection in Stage II Testis Cancer - Basiri, Abbas; Asl-Zare, Mohammad; Mohammadi Sichani, Mehrdad; Djaladat, Hooman (Urology Journal, 2010)
PURPOSE: We report our experience with laparoscopic bilateral retroperitoneal lymph node dissection (RPLND) in 4 patients with stage II testis cancer. MATERIALS AND METHODS: Between January 2002 and January 2009, 4 patients with stage II testis cancer underwent laparoscopic bilateral RPLND. In 2 patients, laparoscopic bilateral RPLND was performed for residual mass post-chemotherapy. We performed classic bilateral RPLND without patient repositioning. RESULTS: The procedure was done uneventfully without any major perioperative complication. The demanding part was contralateral, depending side dissection, which was accomplished with the help of a bowel retractor. Patient repositioning was not necessary. CONCLUSION: Laparoscopic bilateral RPLND can be performed efficiently and safely in stage II testis cancer, without need to repositioning and placement of trocar in contralateral side.